In some Languages, /s/ is a Vowel - Heather Goad; Akiko Shimada (Amherst demo, 2014)
In clusters, /s/ fails to respect the phonotactic constraints of other obstruents; for example, /s/+stop, the optimal sC cluster, does not involve rising sonority. In research that adopts an articulated view of the syllable, the behaviour of /s/ has been captured through assigning it some special status, for example, as an appendix in sC clusters. No proposal along these lines contests the position that /s/ is an obstruent. However, what makes /s/ different from other obstruents is that, like a vowel, it has robust internal cues for place and manner, which ensures its perceptibility, even when adjacent to stops. This paper examines /s/ in Blackfoot (Algonquian), which goes well beyond the appendix-like behaviour this segment shows in other languages. We propose that this is because Blackfoot /s/ is a vowel: it can be underlyingly non-moraic (akin to a glide), monomoraic or bimoraic. Depending on its position in the string, moraic /s/ will surface as a syllable head and/or coda, sometimes with links to preceding or following onsets as well. None of this, we argue, has to be stipulated: combined with ordinary constraints on syllabification (place, sonority and hiatus), the segmental context in which /s/ occurs determines its realization.
Keywords: Blackfoot; Algonquian; syllabification; Moraic Theory; /s/; Strident Vowels